Peningkatan Hasil Belajar IPA Materi Ciri-ciri Khusus Makhluk Hidup Melalui Penerapan Puzzle Picture Game Pada Siswa Sekolah Dasar - Zulhaini, Zulhaini (Yayasan Darussalam Bengkulu, 2022)
This research aims to improve the learning outcomes of 6th Grade students of Public Elementery School 01 Mukomuko City through puzzle pictured games in the material of special characteristics of living things. The collaboration or discussion activities carried out in the first cycle are still dominated by a number of students. Students who appear to speak to that and students who are at the lower level are still shy to express their opinions. While in the second cycle students become more active, motivated, more challenged to learn, positive attitudes appear and less negative attitudes. Students are more often actively involved in drawing up puzzles, interacting with group friends and caring about their friends, active in class discussions and diligently reading sourcebooks to solve questions in the student worksheets. The final test results of learning in the initial conditions before being given an action only reached an average value of 56.25 with only 29.2% (7 students) completing the minimum criteria. At the end of the first cycle learning test, there was an increase in the average value of students 68.75 with mastery learning by 70.8% (17 students). This means that 7 students have not yet reached the minimum criteria that have been set ie 70.00. Therefore researchers need to continue the second cycle by improving the learning process in accordance with the results of the reflection of the first cycle of activities. In the second cycle, the average value of students has reached 85.4 shows that the learning process of the second cycle has shown a very sharp improvement, where mastery learning achieved even exceeding the target set. All this is caused by the involvement and seriousness of students in discussions getting higher.